Seroprevalence of leptospiral antibodies and knowledge, attitude and practices of leptospirosis to non high risk group in Selangor - S. N. S., Sakinah; S., Suhailah; Tengku Jamaluddin, Tengku Zetty Maztura; Masri, Siti Norbaya; Osman, Malina (Community Health Society Malaysia (CHSM), 2015)
Background: Leptospirosis has become an urban public health problem as the rural poor population has moved into the cities. It is not much known about seropositivity among community and factor associated with leptospirosis. This study aims to determine the seroprevalence of leptospiral antibodies and its association between identified risk factors and exposure to rodents as well as to determine knowledge, attitude, and practice (KAP) level among non high risk group in Selangor.